A Parallel Approach of Simulated Annealing Using GPGPU to Solve the Quadratic Assignment Problem - Takemoto, Lucas Arakaki; Dantas, Bianca de Almeida; Mongelli, Henrique (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2018: Anais do XIX Simpósio em Sistemas Computacionais de Alto Desempenho, 2018)
In the area of combinatorial optimization, the Quadratic Assignment Problem stands out due to its complexity and its range of applications. The main goal of this work, is to analyze the performance of Simulated Annealing when applied to the QAP. In an attempt to achieve better results, besides the sequential implementations, parallel strategies using GPUs have also been adopted.